Stress Relaxation by Addition-Fragmentation Chain Transfer in Highly Crosslinked Thiol-Yne Networks - Park, Hee Young (2010)
Radical mediated addition-fragmentation chain transfer of mid-chain allyl sulfide functional groups was utilized to reduce polymerization-induced shrinkage stress in thiol-yne step-growth photopolymerization reactions. In previous studies, the addition-fragmentation of allyl sulfide during the polymerization of a step-growth thiol-ene network demonstrated reduced polymerization stress; however, the glass transition temperature of the material was well below room temperature (~ −20°C). Many applications require super-ambient glass transition temperatures, such as microelectronics and dental materials. Polymerization reactions utilizing thiol-yne functional groups have many of the advantageous attributes of the thiol-ene-based materials, such as possessing a delayed gel-point, resistant to oxygen inhibition, and fast reaction kinetics, while also possessing a high glass transition temperature. Here we incorporate allyl sulfide functional groups into a highly crosslinked thiol-yne network to reduce polymerization-induced shrinkage stress. Simultaneous shrinkage stress and functional group conversion measurements were performed during polymerization using a cantilever-type tensometer coupled with a FTIR spectrometer. The resulting networks were highly crosslinked, possessed super-ambient glass transition temperatures, and exhibited significantly reduced polymerization-induced shrinkage stress when compared with analogous propyl sulfide-containing materials that are incapable of addition-fragmentation.